Social Policy in the Implementation of Concurrent Government Affairs in the Nias Archipelago Area, Indonesia - Ali Mukti Tanjung; Gunawan Undang; Aji Primanto (UIN Sunan Gunung Djati, 2023)
The implementation of social policies for Concurrent Government Affairs in the Nias Archipelago Area, Sumatera Utara Province, is still experiencing inequality, especially from the aspect of budget allocation. This article aims to analyze these problems, using a qualitative descriptive method, data sourced from the Ministry of Finance of the Republic of Indonesia (2022). We use data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed that (1) out of 33 regencies/cities in Sumatera Utara Province, 5 regencies/cities in the Nias Archipelago Area, namely Nias Regency, Nias Selatan Regency, Nias Utara Regency, Nias Barat Regency, and Gunungsitoli City experienced significant imbalances in budget extreme allocations with 28 non-island (mainland) regions and below the provincial average. The lack of social policies will have a significant effect on the implementation of Optional Concurrent Government Affairs in the archipelago; and (2) Conceptually, it is important to pay attention to the principles of accountability, efficiency, externality, and national strategic interests in treating archipelagic areas through increased transfer funds – including the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) - as specifically regulated in Law Number 23 of 2014 concerning Local Government. It is hoped that the novelty of this research can become material for evaluating policies of the central and provincial governments. This research can have implications for accelerating development, especially in island areas.